Hepatic CREBZF couples insulin to lipogenesis by inhibiting insig activity and contributes to hepatic steatosis in diet‐induced insulin‐resistant mice. Issue 4 (18th May 2018) - Zhang, Feifei; Hu, Zhimin; Li, Gaopeng; Huo, Shaofeng; Ma, Fengguang; Cui, Aoyuan; Xue, Yaqian; Han, Yamei; Gong, Qi; Gao, Jing; Bian, Hua; Meng, Zhuoxian; et al.
Abstract : Insulin is critical for the regulation of de novo fatty acid synthesis, which converts glucose to lipid in the liver. However, how insulin signals are transduced into the cell and then regulate lipogenesis remains to be fully understood. Here, we identified CREB/ATF bZIP transcription factor (CREBZF) of the activating transcription factor/cAMP response element‐binding protein (ATF/CREB) gene family as a key regulator for lipogenesis through insulin‐Akt signaling. Insulin‐induced gene 2a (Insig‐2a) decreases during refeeding, allowing sterol regulatory element binding protein 1c to be processed to promote lipogenesis; but the mechanism of reduction is unknown. We show that Insig‐2a inhibition is mediated by insulin‐induced CREBZF. CREBZF directly inhibits transcription of Insig‐2a through association with activating transcription factor 4. Liver‐specific knockout of CREBZF causes an induction of Insig‐2a and Insig‐1 and resulted in repressed lipogenic program in the liver of mice during refeeding or upon treatment with streptozotocin and insulin. Moreover, hepatic CREBZF deficiency attenuates hepatic steatosis in high‐fat, high‐sucrose diet–fed mice. Importantly, expression levels of CREBZF are increased in livers of diet‐induced insulin resistance or genetically obese ob/ob mice and humans with hepatic steatosis, which may underscore the potential role of CREBZF in the development of sustained lipogenesis in the liver under selective insulin resistance conditions. Conclusion : These findings uncover an unexpected mechanism that couples changes in extracellular hormonal signals to hepatic lipid homeostasis; disrupting CREBZF function may have the therapeutic potential for treating fatty liver disease and insulin resistance. (Hepatology 2018).